Herbal Remedies : Dozens of safe, effective treatments to grow and make - Fisher, Katheen (Rodale'es Essential Herbal HanBooks, 1999)
herbs,--Herbal healing formulas.--Essential healing herbal,--Essential healing herbs A to Z.--Growing healing herbs.--Symptoms and remedies.--Herbal resources.